2014
DOI: 10.1016/j.abb.2014.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of ER stress and activation of apoptotic pathways in fisetin induced cytotoxicity in human melanoma

Abstract: The prognosis of malignant melanoma remains poor in spite of recent advances in therapeutic strategies for the deadly disease. Fisetin, a dietary flavonoid is currently being investigated for its growth inhibitory properties in various cancer models. We previously showed that fisetin inhibited melanoma growth in vitro and in vivo. Here, we evaluated the molecular basis of fisetin induced cytoxicity in metastatic human melanoma cells. Fisetin treatment induced endoplasmic reticulum (ER) stress in highly aggress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
46
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 46 publications
3
46
1
Order By: Relevance
“…It was reported that chemotherapeutic agents induced necrotic or apoptotic cell death in cancer cells via the generation of ROS (41). But another report showed that fisetin treatment of A375.S2 melanoma cells resulted in a significant decrease in ROS level (28), while another reported that fisetin stimulated generation of ROS in U266 multiple myeloma cells and induced apoptosis through activation of AMP-activated protein kinase pathways in a ROS-dependent manner (42). Thus, based on these observations, fisetininduced modulation of ROS may be cell type-dependent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that chemotherapeutic agents induced necrotic or apoptotic cell death in cancer cells via the generation of ROS (41). But another report showed that fisetin treatment of A375.S2 melanoma cells resulted in a significant decrease in ROS level (28), while another reported that fisetin stimulated generation of ROS in U266 multiple myeloma cells and induced apoptosis through activation of AMP-activated protein kinase pathways in a ROS-dependent manner (42). Thus, based on these observations, fisetininduced modulation of ROS may be cell type-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports have shown that fisetin induced cytotoxic effects on many human cancer cell lines through cell-cycle arrest and apoptosis (20,(22)(23)(24)(25)(26)(27)(28)(29), however, there is no report demonstrating that fisetin induces apoptosis of human oral cancer cells, therefore, we investigated the cytotoxic effects of fisetin on HSC3 human oral cancer cells in vitro. It is well documented that the best strategy for anticancer drugs is to induce cancer cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its anti-oxidant activity, we [3,5,2631] and others [4,7] have extensively shown the potential of fisetin in affecting signaling pathways that control cell survival, growth and proliferation both in vitro and in vivo . Haddad et al [7] observed a decrease in proliferation with concomitant induction of apoptosis in prostate cancer cells upon fisetin treatment.…”
Section: Anti-cancer Activity Of Fisetinmentioning
confidence: 99%
“…In addition, the sensitivity of cancer cells to apoptosis in vitro may be a predictor of their sensitivity to these drugs in vivo . We [3,5,28] and others [4,6,34,42,66] have shown that fisetin has significant pro-apoptotic activities against cancer cells. A structure-activity relationship study of 22 flavonoids showed that at least two hydroxylations in positions 3, 5, and 7 of the A ring were needed to induce apoptosis, whereas hydroxylation in 3' and/or 4' of the B ring enhanced proapoptotic activity [70].…”
Section: Anti-cancer Activity Of Fisetinmentioning
confidence: 99%